PERCEPTION OF JOB ROTATION AS A CAREER ENHANCEMENT EFFORT: A CASE STUDY AT THE MEMPAWAH POLICE STATION - Atlantika, Yeremia Niaga; Dewi, Yustina Erti Pravitasmara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Job rotation refers to the rotation of employees in the work environment which has the potential lowering the employee motivation. However, it has several dimensions related to motivation which encourage the employees to do positive things for the organization. This study contributes to the literature explaining the benefit of job rotation which fosters the perspective of promotion within the scope of tour of duty and tour of area. The job rotation has been commonly applied to maintain the police institution’s sustainability and played a role as a promotion for future employees’ career. Further, the job rotation also influences the employees to have a high motivation to work and build good perspectives which simultaneously helps them perform well at work. This research is based on a case study which involved 9 informants as the primary data. The data was analyzed in a qualitative manner using NVivo 12 plus version 2019. The results show that the dimensions of job rotation had supported increasing the motivation to work in the Indonesian National Police, especially in Mempawah, West Kalimantan. Keywords: Job Rotation, Motivation, Tour of Area, Tour of Duty